2015
DOI: 10.1093/eurheartj/ehv177
|View full text |Cite
|
Sign up to set email alerts
|

Uninterrupted rivaroxaban vs. uninterrupted vitamin K antagonists for catheter ablation in non-valvular atrial fibrillation

Abstract: AimsVENTURE-AF is the first prospective randomized trial of uninterrupted rivaroxaban and vitamin K antagonists (VKAs) in patients with non-valvular atrial fibrillation (NVAF) undergoing catheter ablation (CA).Methods and resultsTrial size was administratively set at 250, the protocol-specified target. Events were independently and blindly adjudicated. We randomly assigned 248 NVAF patients to uninterrupted rivaroxaban (20 mg once-daily) or to an uninterrupted VKA prior to CA and for 4 weeks afterwards. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
315
6
26

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 387 publications
(370 citation statements)
references
References 31 publications
8
315
6
26
Order By: Relevance
“…W obserwacyjnych kohortach pacjentów poddawanych ablacji przezcewnikowej w doświadczonych ośrodkach, u których stosowano nieprzerwane leczenie za pomocą NOAC, nie uzyskano danych wskazujących na niekorzystny wpływ takiego postępowania na bezpieczeństwo leczenia [761,763,766,767]. Wyniki pierwszej kontrolowanej próby klinicznej, w której porównywano nieprzerwane leczenie za pomocą NOAC i VKA u pacjentów poddawanych ablacji AF, do której włączono ok. 200 osób, niedawno opublikowano [768], podobnie jak kilka doniesień z obserwacyjnych baz danych [761,769,770]. Trwają kolejne próby kliniczne służące porównaniu nieprzerwanego leczenia za pomocą VKA i NOAC u pacjentów z AF poddawanych ablacji, np.…”
Section: Leczenie Przeciwzakrzepowe Przed Ablacją Podczas Ablacji I unclassified
“…W obserwacyjnych kohortach pacjentów poddawanych ablacji przezcewnikowej w doświadczonych ośrodkach, u których stosowano nieprzerwane leczenie za pomocą NOAC, nie uzyskano danych wskazujących na niekorzystny wpływ takiego postępowania na bezpieczeństwo leczenia [761,763,766,767]. Wyniki pierwszej kontrolowanej próby klinicznej, w której porównywano nieprzerwane leczenie za pomocą NOAC i VKA u pacjentów poddawanych ablacji AF, do której włączono ok. 200 osób, niedawno opublikowano [768], podobnie jak kilka doniesień z obserwacyjnych baz danych [761,769,770]. Trwają kolejne próby kliniczne służące porównaniu nieprzerwanego leczenia za pomocą VKA i NOAC u pacjentów z AF poddawanych ablacji, np.…”
Section: Leczenie Przeciwzakrzepowe Przed Ablacją Podczas Ablacji I unclassified
“…This recommendation was in part put forth through studies such as the COMPARE trial, 7 Re-Circuit study, 8 and Venture-AF. 9 The COMPARE trial investigators showed that AF ablation without warfarin discontinuation reduces the occurrence of periprocedural stroke and minor bleeding complications compared with ''bridging'' with low-molecular-weight heparin. The ReCircuit trial was a head-to-head comparison study on the performance of AF ablation on patients receiving uninterrupted dabigatran versus uninterrupted warfarin that found that the incidence of major bleeding events during and up to eight weeks following ablation was significantly lower among the study patients taking dabigatran than those taking warfarin.…”
Section: Anticoagulation Therapymentioning
confidence: 99%
“…14 During the year 2015, several subgroup analyses of the large NOAC trials have surfaced, including bleeding management and outcome with apixaban, 15 the management of rivaroxaban around catheter ablation for AF (VENTURE-AF), 16 and the outcome of amiodarone co-medication in patients receiving edoxaban, 17 to name just a few. Virtually, all subgroups of the large NOAC trials indicate a consistent benefit and safety of these drugs compared with warfarin, further underlining their overall superiority.…”
Section: Stroke Preventionmentioning
confidence: 99%